Novel N-modified glycines based on a (1S, 2S)-2-amino-1-(4-nitrophenyl)propane-1, 3-diol skeleton: 1, 3-dioxanes and tripodands. Issue 51 (21st December 2016) - Moldovan, Oana; Albert, Katalin; Nagy, Iulia; Morar, Cristina; Sacalis, Carmen; Darabantu, Mircea
Graphical abstract: Highlights: A difference between N -alkylating (ClCH2 COOH vs. BrCH2 COOEt) reagents was observed. The appropriate proton scavengers were Na2 CO3 and DIPEA, respectively. The above change relies on the nature of amino-substrate: acyclic vs. cyclic. Saponification of cyclic N -modified glycine esters is a case to case situation. N -Modified glycines based amino-1, 3-dioxane as tripodands requires a multistep synthesis. Abstract: Starting from (1 S, 2 S )-2-amino-1-(4-nitrophenyl)propane-1, 3-diol ( p -nitrophenylserinol, a waste optical antipode product from chloromycetin production) or its 5-amino-1, 3-dioxane derivatives, we report preliminary data concerning the conversion of these optically active substrates into novel N -modified glycines by chemoselective N -monoalkylation with haloacetic ester or acid (X-CH2 COOR, X: Cl, Br; R: Et, H) reagents. The results are discussed in terms of the starting material nature (cyclic vs. acyclic), the steric hindrance in the C -substituted 5-amino-1, 3-dioxanes determining the reactivity of the amino-group and the stability of the intermediates. The synthesis of the first tripodands incorporating N -modified glycine motifs as peripheral units is also reported.